The truth about stacey ebook - Telgemeier, Raina (Baby-Sitters Club Graphic Novel, 2015)
A graphic novel adapted and illustrated by Raina Telgemeier, the #1 New York Times bestselling, multiple Eisner Award-winning author of Smile ! Poor Stacey. She just moved to a new town, is still coming to terms with her diabetes, and is facing baby-sitting problems left and right. Fortunately, Stacey has three new friends — Kristy, Claudia, and Mary Anne. Together they're the BSC — and they will deal with whatever's thrown their way... even if it's a rival baby-sitting club!